2017
DOI: 10.1080/01635581.2018.1397709
|View full text |Cite
|
Sign up to set email alerts
|

FTO Gene Affects Obesity and Breast Cancer Through Similar Mechanisms: A New Insight into the Molecular Therapeutic Targets

Abstract: The FTO gene may has a critical role in obesity and breast cancer. Similar molecular mechanisms may play a role in the development of breast cancer and obesity. If this result is correct then, it will be interesting to examine the FTO gene as a molecular therapeutics target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 42 publications
0
33
1
2
Order By: Relevance
“…It is possible that the FTO gene polymorphism can modify the effects of diet on the FTO gene expression [ 28 ]. Although recent studies suggested that FTO has an effect on BMI, at least partly, through the change in the expression levels of other obesity-related genes such as IRX3 [ 29 30 ], Moreover, a complete LD was found in the present study between three neighboring SNPs of the first intron region of the FTO gene. Although the linkage disequilibrium (LD) between rs9930506, rs9930501 and rs9932754 has been reported in genome-wide association studies [ 22 , 31 , and 32 ].…”
Section: Discussioncontrasting
confidence: 72%
“…It is possible that the FTO gene polymorphism can modify the effects of diet on the FTO gene expression [ 28 ]. Although recent studies suggested that FTO has an effect on BMI, at least partly, through the change in the expression levels of other obesity-related genes such as IRX3 [ 29 30 ], Moreover, a complete LD was found in the present study between three neighboring SNPs of the first intron region of the FTO gene. Although the linkage disequilibrium (LD) between rs9930506, rs9930501 and rs9932754 has been reported in genome-wide association studies [ 22 , 31 , and 32 ].…”
Section: Discussioncontrasting
confidence: 72%
“…In another study carried out by Li et al, high expression of FTO with t(11q23) rearrangements has been observed to regulate the expression of ASB2 and RARA, leading to cell transformation and leukemogenesis in acute myeloid leukemia (AML) [88]. In addition, recently two different association studies by Salgado-Montilla et al in a cohort of Puerto Rican men and Akbari et al from literature survey, also reported causal link between FTO and cancer onset as well as progression [89, 90]. In a breast cancer biopsies study carried out by Zhang et al, a concordance of ALKBH5 and HIF-1a expression has been reported, suggesting hypoxia dependent regulation of ALKBH5.…”
Section: Alteration Of Modification Enzymes and Their Marks In Diseasesmentioning
confidence: 99%
“…A study by Guo and colleagues showed that FOXA2 overexpression was associated with significant downregulation of FTO promoter activity whereas FOXA2 depletion allowed FTO expression, thereby providing evidence that FOXA2 is a negative repressor of the FTO gene ( Guo et al, 2012 ). FTO was previously shown to be involved in several metabolic syndrome-related conditions such as diabetes, insulin signaling, lipogenesis, and mitochondrial dysfunction, whereby FTO overexpression was observed ( Bravard et al, 2011 ; Akbari et al, 2018 ). In this case, the lack of appropriate repressor response was associated with untimely expression of target genes, which resulted in clinical manifestation of diseases.…”
Section: Control Of Transcription By Trans-regulatory mentioning
confidence: 99%